Downregulation of Brain Enriched Type 2 MAGEs Is Associated With Immune Infiltration and Poor Prognosis in Glioma - Arora, Mohit; Kumari, Sarita; Singh, Jay; Chopra, Anita; Chauhan, Shyam S. (Frontiers in Oncology, 2020)
Melanoma associated antigen (MAGE) is an extensively studied family of tumor-associated genes that share a common MAGE homology domain (MHD). Based upon their expression pattern, MAGE genes have been broadly classified into type 1 MAGEs (T1Ms) and type 2 MAGEs (T2Ms) categories. Interestingly, several T2Ms are highly expressed in the brain and involved in the regulation of neuronal development, differentiation, and survival. Available literature suggests possible tumor suppressor functions of a few T2Ms, while information available about their expression, regulation, and clinical significance in glioma is scanty. This prompted us to perform a comprehensive analysis of T2M expression in glioma. Gene expression data from glioma datasets: Oncomine, TCGA, and REMBRANDT study, were used to assess the mRNA expression of T2M genes (MAGED1, MAGED2, MAGED3, MAGED4, MAGED4B, MAGEE1, MAGEE2, MAGEF1, MAGEH1, MAGEL2, NSMCE3, and NDN), and their association with clinical characteristics and composition of the tumor microenvironment. Further, mutation, copy number alteration, and DNA methylation data from TCGA were assessed for determining potential mechanisms of T2Ms expression in glioma. Expression analysis revealed overexpression of MAGED subfamily genes in glioma, while other genes of this family exhibited reduced expression in advanced grades of this malignancy. Further, the expression of T2Ms exhibited varying extent of positive correlations with each other. Amongst downregulated T2Ms, MAGEH1 expression exhibited negative correlations with DNA methylation. Additionally, genes associated with MAGEH1 were enriched in Myc and Hedgehog signaling. Furthermore, T2Ms downregulation was associated with immune infiltration in glioma tissues and poor overall survival of glioma patients. In multivariate Cox regression analysis, MAGEH1 emerged as an independent prognosticator in lower grade glioma. Conclusively, these results suggest that expression of T2Ms is associated with important clinical and molecular features in glioma. Mechanistic studies may further provide novel insights into their role in glioma progression.